Ancient Civilizations - Scarre,Chris (Routledge, 2018)
Ancient Civilizations offers a comparative analysis of the field, including both old world and new civilizations, and explores the connections between all civilizations around the earth. The volume provides a jargon-free introduction to ancient civilizations from the first civilizations, and the great powers in the Near East, to the first Aegean civilizations, the Mediterranean world in the first millennium, Imperial Rome, northeast Africa, divine kings in southeast Asia, and empires in East Asia, as well as early states in the Americas and Andean civilization. For those interested in ancient civilizations.